Selenium and tellurium derivatives of corannulene: serendipitous discovery of a one-dimensional stereoregular coordination polymer crystal based on Te-O backbone and side-chain aromatic array - Barát, Viktor (2022)
Monobromo-, tetrabromo-, and pentachloro-corannulene are subjected to nucleophilic substitution reactions with tolyl selenide and phenyl telluride-based nucleophiles generated in situ from the corresponding dichalcogenides. In the case of selenium nucleophile, the reaction provides moderate yields (52-77 %) of the targeted corannulene selenoethers. A subsequent oxidation of the selenium atoms proceeds smoothly to furnish corannulene selenones in 81-93 % yield. In the case of tellurides, only monosubstitution of the corannulene scaffold could be achieved albeit with concomitant oxidation of the tellerium atom. Unexpectedly, this monotelluroxide derivative of corannulene (RR'Te=O, R=Ph, R'=corannulene) is observed to form a linear coordination polymer chain in the crystalline state. In this chain, Te-O constitutes the polymer backbone around which the aromatic groups (R and R') arrange as polymer side-chains. The polymer crystal is stabilized through intramolecular π-π stacking interactions of the side-chains and intermolecular hydrogen and halogen bonding interactions with the solvent (chloroform) molecules. Interestingly, each diad of the polymer chain is racemic. Therefore, in terms of stereoregularity, the polymer chain can be described as syndiotactic.